LITERASI MEDIA KHALAYAK DI ERA KEBERLIMPAHAN INFOMASI DI MEDIA MASSA - Robeet Thadi (JURNAL ILMIAH SYI'AR, 2019)
The era of information abundance problems has shifted, from the difficulty offinding information to the difficulty of filtering information. This paper aims toexplain the urgency of public media literacy in the midst of the abundance ofinformation presented by the mass media. Media literacy is a concept about the ways people question what is watched, observed, read and produced from the media. Media literacy is needed so that the public as a media audience has the authority to actively sort out and choose media shows, so that if there is a presentation that only emphasizes sensation, the public can reject it. by not watching it or switching to other shows. The public can control the contents of the media critically and intelligently so that they can detect propaganda, certain interests or bias in the appearance of the media